Assessing Cultural Competence in Healthcare Settings at a Faith-Based Maternal and Child Hospital in Indonesia: A Cross-Sectional Study - Rahman, Ferry Fadzlul (Universitas Muhammadiyah Yogyakarta, 2026)
This study aimed to analyze the relationships among cultural awareness, cultural knowledge, cultural skills, cultural interaction, and cultural motivation with work culture competence among healthcare workers at Aisyiyah Mother and Child Hospital, Samarinda. This study employed a cross-sectional design involving 44 healthcare workers as respondents. The sampling technique used was stratified random sampling. Data were collected through questionnaires and analyzed using Spearman’s rank test and multiple logistic regression. The findings revealed that all independent variables were significantly related to work culture competence (p-values < 0.05). The R-square value of 42% indicated the contribution of these variables in explaining cultural competence. The regression analysis identified cultural interaction as the variable with the strongest association with cultural competence (aOR = 11.376), followed by cultural knowledge and cultural awareness. This result indicates that several interrelated cultural factors contribute to the development of healthcare workers’ cultural competence. Efforts to enhance cultural competence through continuous training and mentorship should be implemented to improve the quality of healthcare services in hospitals that are grounded in Islamic values.